Influence of drill speed and feed rate on bone damage - Fernandes, M.G.A. (2016)
Implant failures and postoperative complications are often associated to the bone drilling. Estimation and control of drilling parameters are critical to prevent mechanical damage to the bone tissues. For better performance of the drilling procedures, it is essential to understand the mechanical behaviour of bones that leads to their failures and consequently to improve the cutting conditions. This paper investigates the effect of drill speed and feed-rate on mechanical damage during drilling of solid rigid foam materials, with similar mechanical properties to the human bone. Experimental tests were conducted on biomechanical blocks instrumented with strain gauges to assess the drill speed and feed-rate influence. A three-dimensional dynamic finite element model to predict the bone stresses, as a function of drilling conditions, drill geometry and bone model, was developed. These simulations incorporate the dynamic characteristics involved in the drilling process. The element removal scheme is taken into account and allows advanced simulations of tool penetration and material removal. Experimental and numerical results show that generated stresses in the material tend to increase with tool penetration. Higher drill speed leads to an increase of von-Mises stresses and strains in the solid rigid foams. However, when the feed-rate is higher, the stresses and strains are lower. The numerical normal stresses and strains are found to be in good agreement with experimental results. The models could be an accurate analysis tool to simulate the stresses distribution in the bone during the drilling process.